Post a New Question


posted by on .

Rewrite with positive exponents. Assume that even roots are of nonnegative quantities and that all denominators are nonzero.

  • Algebra - ,

    (3Y(2/3))^-3 =
    (6Y/3)^-3 =
    (2Y)^-3 = 2^-3Y^-3 = 1/(2^3Y^3)=1/8Y^3.

  • Algebra 2 - ,

    (3y 2/3)-3
    rewrite with positive exponents. assume that even roots are nonzero quantities and the denominator are nonzero

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question